Friedrich List and the Imperial origins of the national economy - INCE, Onur Ulas (Institutional Knowledge at Singapore Management University, 2016)
This essay offers a critical reexamination of the works of Friedrich List by placing them in the context of nineteenth-century imperial economies. I argue that List's theory of the national economy is characterised by a major ambivalence, as it incorporates both imperial and anti-imperial elements. On the one hand, List pitted his national principle against the British imperialism of free trade and the relations of dependency it heralded for late developers like Germany. On the other hand, his economic nationalism aimed less at dismantling imperial core-periphery relations as a whole than at reproducing these relations domestically and expanding them globally. I explain this ambivalence with reference to List's designation of imperial Britain as the prime example of successful economic development and a model to be emulated by late industrialisers. List thereby fashioned his ideas on national development out of the historical experience of an empire whereby he internalised its economic logic and discourse of the civilising mission. Consequently, List's national economy culminated in an early vision of the global north-south relations, in which the global industrial-financial core would expand to include France, Germany and the USA, while the rest of the world would be reduced to quasi-colonial agrarian hinterlands.